Habitat suitability modeling for Posidonia oceanica distribution along a Mediterranean region (NW Italy) - Rachele Bordoni; Chiara Paoli; Monica Montefalcone; Alice Oprandi; Ilaria Rigo; Francesca Ruggeri; Paolo Vassallo (Environmental and Sustainability Indicators)
Posidonia oceanica (L.) Delile is a keystone seagrass species, playing a central role in the ecological balance of Mediterranean coastal areas but threatened by increasing human pressures. Proper management and conservation of coastal marine habitats require the understanding of its distribution. To address this need, we developed habitat suitability models (HSMs), built up using the Random Forest algorithm in R software, that assess the suitability of the environment for the presence of P. oceanica in the Ligurian Sea (NW Italy).Model response variables included potential seabed areas characterized by P. oceanica habitats on soft and rocky bottoms, down to 50 m depth. Explanatory variables included natural factors as well as variables related to human activities along the coastal strip.The HSMs showed high accuracy rates of 82% for P. oceanica on soft bottom and 99% for P. oceanica on rocky bottom. The models predict an increase in P. oceanica meadows on soft bottom, from 2448 ha to 11623 ha, and a modest increase on rocky bottom, from 159 ha to 200 ha. The west coast of Liguria was found to have a greater extent of seagrass meadows compared to the east coast.This study provides valuable guidance for the sustainable management of P. oceanica meadows and offers practical tools for scientific research, land managers, stakeholders, and policy makers. These findings are essential for the conservation of a vital marine ecosystem and for promoting prudent and effective land management, ultimately securing the legacy of P. oceanica in northwestern Italy.